A Comparative Study between Universal Eclectic Septoplasty Technique and Cottle - Amaral Neto,Odim Ferreira do (2017)
Abstract Introduction Since the last century surgical correction of nasal septum deviation has been improved. The Universal Eclectic Technique was recently reported and there are still few studies dedicated to address this surgical approach. Objective The objective of this study is to compare the results of septal deviation correction achieved using the Universal Eclectic Technique (UET) with those obtained through Cottle’s Technique. Methods This is a prospective study with two consecutive case series totaling 90 patients (40 women and 50 men), aged between 18 and 55 years. We divided patients into two groups according to the surgical approach. Fifty-three patients underwent septoplasty through Universal Eclectic Technique (UET) and thirty-seven patients were submitted to classical Cottle’s septoplasty technique. All patients have answered the Nasal Obstruction Symptom Evaluation Scale (NOSE) questionnaire to assess pre and postoperative nasal obstruction. Results Statistical analysis showed a significantly shorter operating time for the UET group. Nasal edema assessment performed seven days after the surgery showed a prevalence of mild edema in UET group and moderate edema in Cottle’s technique group. In regard to complication rates, UET presented a single case of septal hematoma while in Cottle’s technique group we observed: 02 cases of severe edemas, 01 case of incapacitating headache, and 01 complaint of nasal pain. Conclusion The Universal Eclectic Technique (UET) has proven to be a safe and effective surgical technique with faster symptomatic improvement, low complication rates, and reduced surgical time when compared with classical Cottle’s technique.